2021
DOI: 10.1002/cae.22382
|View full text |Cite
|
Sign up to set email alerts
|

Computational thinking: Enhancing STEAM and engineering education, from theory to practice

Abstract: This publication provides an editorial introduction to a special issue of Computer Applications in Engineering Education journal entitled Computational Thinking for STEM and Engineering Education. It provides introductory remarks to the issue and a commentary on the published material, as well as presents the views of the special issue editors in the field of science, technology, engineering and mathematics (STEM) education and research. This special issue is structured as follows. It contains articles related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 5 publications
0
24
0
2
Order By: Relevance
“…From the aspect of the application, STEM and STEAM education have also seen the differences. STEAM education strengthens STEM education 5 / 19 (Bahrum et al, 2017;Dolgopolovas & Dagienė, 2021), whereby the identified differences are the extra characteristics found in STEAM education and not in STEM. Firstly, STEM education demonstrates the understanding of science and mathematics standards being taught in the classroom, whereas STEAM education uses the arts to demonstrate understanding of science and mathematics standards being taught in the classroom (Moore et al, 2014).…”
Section: It Is Steam and Not Stemmentioning
confidence: 95%
See 2 more Smart Citations
“…From the aspect of the application, STEM and STEAM education have also seen the differences. STEAM education strengthens STEM education 5 / 19 (Bahrum et al, 2017;Dolgopolovas & Dagienė, 2021), whereby the identified differences are the extra characteristics found in STEAM education and not in STEM. Firstly, STEM education demonstrates the understanding of science and mathematics standards being taught in the classroom, whereas STEAM education uses the arts to demonstrate understanding of science and mathematics standards being taught in the classroom (Moore et al, 2014).…”
Section: It Is Steam and Not Stemmentioning
confidence: 95%
“…Concentrating on a single subject and combining all the five disciplines into one item without losing the initial quality and learning objectives is challenging (Conde et al, 2019). The unsuitable teaching method caused confusion and misconception for the scientific concepts and consequently deteriorated the enthusiasm in learning (Dolgopolovas & Dagienė, 2021).…”
Section: Research Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the main problem while studying CT and its educational realm is the apparent controversy between two (at the least) practical attitudes, where the first one is focused on the operational aspects and the second on the developmental aspects [24][25][26]. This is a fundamental watershed, and we argue that it is based on fundamental differences in worldviews and approaches to the aims and objectives of education.…”
Section: Introductionmentioning
confidence: 92%
“…Si trasladamos esto a un entorno educativo las posibilidades que ofrece esta metodología son rápidamente apreciables: más allá del aprendizaje y la puesta en práctica de habilidades para resolver problemas en contextos reales, los alumnos tienen no sólo una magnífica oportunidad para aprender y utilizar técnicas de design thinking, aprendizaje basado en proyectos, trabajo colaborativo y habilidades de comunicación, sino también la posibilidad de abordar un proyecto desde el enfoque STEM (por sus siglas en inglés: Science, Technology, Engineering and Maths) en el que las Ciencias, la Tecnología, la Ingeniería y las Matemáticas se trabajan como una sola disciplina permitiendo profundizar en la esencia del problema y en las necesidades que éste plantea (Dolgopolovas y Dagienė 2021). En el trabajo Porras y col. 2018 los autores presentan una taxonomía de los diferentes tipos de hackatons.…”
Section: Introductionunclassified